Hypercoordinated Fluoro(pentafluoroethyl)stannanes and ‐stannates. Issue 35 (26th August 2018) - Klösener, Johannes; Wiesemann, Markus; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract : The treatment of phenyl‐protected pentafluoroethylstannanes, Sn(C2 F5 )4– n Ph n ( n = 1–3), with anhydrous HF results in the formation of the corresponding fluorostannanes which are associated in the solid state but form monomeric and dimeric fluoride complexes in solution. Due to the pronounced Lewis acidity caused by the electron‐withdrawing pentafluoroethyl groups, these stannanes represent suitable precursors for the synthesis of neutral, monoanionic and dianionic hexacoordinate tin(IV) complexes. The employment of an excess of cesium fluoride and 1, 10‐phenanthroline exclusively leads to the octahedral complexes [Sn(C2 F5 ) n F6– n ] 2– ( n = 2–4) and [Sn(C2 F5 ) n F4– n (phen)] ( n = 1–3). The addition of bases, donating solvents as well as LiF, on the other hand, selectively affords salts containing dinuclear anions of the form [(C2 F5 )3 Sn(µ‐F)3 Sn(C2 F5 )3 ] – and [(C2 F5 )2 F2 Sn(µ‐F)2 SnF2 (C2 F5 )2 ] 2– . Abstract : Treatment of phenyl protected pentafluoroethylstannanes (C2 F5 )4– n SnPh n ( n = 1–3) with anhydrous HF results in the formation of the corresponding fluorostannanes. Due to the pronounced Lewis acidity caused by the electron‐withdrawing pentafluoroethyl groups these stannanes represent suitable precursors for the synthesis of neutral, mono‐ and dianionic hexacoordinate tin(IV) complexes.